ANTAGONISTIC ACTIVITY OF MARINE BACTERIA FROM KARIMUN ISLAND, INDONESIA - Ruby Setiawan; Ade Lia Putri; Mia Kusmiati (BERITA BIOLOGI, 2022)
Antimicrobial resistance (AMR) is becoming a major global crisis in the public healthcare system. One of the issues is the misuse of antimicrobials that will accelerate the AMR phenomenon. Discovering new antimicrobial compounds from various sources and places is an alternative way to resolve this problem. Marine bacteria were known as a new promising source for bioactive compounds. The marine bacteria were isolated from marine sediment using 1/5 NBRC 802 agar and seawater agar supplemented with 10mM NH4Cl. All isolates were subjected to antagonistic activity against Escherichia coli, Bacillus subtilis, and Staphylococcus aureus using the disk diffusion method. The selected isolates were then identified based on the 16S rRNA gene sequence. A total of 65 bacterial isolates have been successfully isolated from the seawater and marine sediment from Karimun Island. Of the 65 isolates, 12 isolates showed activity against tested bacteria; seven isolates against B. subtilis, two isolates against S. aureus, one isolate against E. coli, one isolate against B. subtilis and S. aureus, and one isolate against S. aureus and E. coli. The 16S rDNA sequences showed that the selected isolates belong to Cellulosimicrobium funkei, Gordonia sp., Kocuria salina, Micrococcus aloeverae, Micromonospora aurantiaca, Mumia sp., Nocardioides sp., and Pseudoalteromonas shioyasakiensis. Most of the isolates with antibacterial activity were identified as Actinobacteria and one isolate from the Gammaproteobacteria. Isolate KRSd2(2) shared 97,79% identity with Gordonia bronchialis. Further, a taxonomical study of the isolate compared with known species and chemical analysis of bioactive compounds are needed.